Providing for old age through private channels - Honohan, W. A. (Statistical and Social Inquiry Society of Ireland, 1960)
At a time when a Bill has been introduced into the Dail containing proposals for the inauguration of a contributory pensions scheme, it seems opportune to review the position generally in regard to the problem of old age and the methods of making financial provision for it through private channels. There have been developments in this sphere in recent years, and interest in it has grown for a variety of reasons. The increasing numbers of persons reaching pensionable ages have contributed to a greater awareness of the need for security and adequate standards of living in old age?an awareness no doubt quickened by the war. The consequent growth of pension schemes and arrangements calls for some study of their effect on the economy, and the fall in the value of money presents other problems, including the question as to whether pension schemes should be funded or not.
Read before the Society, 13 May 1960
Keywords: Pensions in Ireland; Private pensions; Economics of pensions; 314.15